Aktivitas Pengembangan Skill, Minat, dan Bakat Cabang Olahraga Atletik pada Anak-anak - Valenska Karunia Salsyahbilla (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Athletics is a sport practiced in various forms, encompassing running, throwing, and jumping. In athletics, there are many disciplines and interpretations that define the sport. Despite sounding unfamiliar and less popular compared to other sports, athletics is the oldest sport and is contested in sporting events. Issues in sports in Mareje Village, Lembar District, West Lombok Regency include: 1) lack of sports facilities such as fields and understanding of several athletic game rules; and 2) inadequate understanding of athletic games, including techniques like running, sprinting, and throwing within the playing method of athletics. The objectives of this activity include: 1) enhancing technical and physical skills in athletic disciplines such as running, jumping, and throwing; 2) fostering children's interest in athletics through direct experience and exploring various aspects of athletic disciplines; and 3) identifying and nurturing children's natural talents in athletics, through systematic and continuous training. Solutions related to facilities and infrastructure involve utilizing the field of SMP Negeri 3 Lembar, West Lombok Regency, and some facilities from the school. At this location, activity organizers provide explanations regarding rules, and conduct training in running techniques, sprinting, and throwing that are effective, appropriate, and correct within the framework of athletic disciplines. The outcomes of this activity include increasing the interest and curiosity of children in Mareje Village in sports activities; this curiosity can lead to positive engagements such as participating in city, provincial, and even national-level competitions.